Two species of Leptographium isolated from blue-stained sapwood of Pinus khasya and bark beetles in Thailand - Yamaoka Y. (2014)
Two species of Leptographium were isolated from blue-stained sapwood of Pinus khasya and bark beetle galleries in pine trees near Chiang Mai, Thailand. Based on morphological observations, these two species were identified as L. pini-densiflorae and L. yunnanense. This is the first record of these fungi in Thailand. Leptographium yunnanense appeared to be associated with Polygraphus major. © 2007 The Mycological Society of Japan and Springer-Verlag.